"I get all my ideas from the tree": investigating elementary students' views as reflexive writers. Issue 2 (4th March 2023) - Khosronejad, M.; Ryan, M.; Barton, G.; Kervin, L.
ABSTRACT: Despite the importance of writing skills to school and life success, there is scant research into the enabling and constraining conditions that shape elementary students' views about their writing practices. This paper examines students' views about writing through the lens of reflexivity theory. Applying an explanatory sequential model of mixed-method design, it first describes the development of a self-report questionnaire to investigate the views of 570 elementary students about themselves as writers. Second, it draws on semi-structured interviews with 46 students across Years 3 to 6. The results show that the majority of students see themselves as autonomous and meta-reflexive writers. In addition, results indicate time, teacher pedagogy and the place to practice writing as contextual conditions experienced by learners and place an emphasis on the personal conditions such as students' lack of confidence, persistence and ideas. We discuss implications for further practice in elementary schools.